Pengembangan Perangkat Pembelajaran Elektronik Berbasis STEAM untuk Meningkatkan Minat dan Hasil Belajar - Herlina, Herlina; Ramlawati, Ramlawati; Hasri, Hasri (Chemistry Education Review (CER), 2022)
This study is a development research that aims to produce STEAM-based electronic learning device on colloid material to increase student’s interest and learning achievement that are valid, practical and effective. The development model uses the ADDIE development model which consists of 5 stages : (1) the analysis phase includes curriculum analysis, student analysis, concept analysis, formulation of learning objectives, and task analysis; (2) the design, which includes the stage of selecting the format and initial design of the RPP, e-module and E-LKPD using the Canva application; (3) the device development stage by integrating STEAM aspects and following the Project Based Learning (PjBL) syntax; (4)the deployment stage is the testing phase of learning tools that have been validated by experts and have been revised by developers; (5) the evaluation phase includes the evaluation of learning devices after going through the trial phase. Analysis of the results of the validation of RPP, e-Modul and e-LKPD based on the STEAM PjBL model, namely 3.53; 3.80; and 3.77 very valid categories. Practical based on the practicality test by looking at the implementation of STEAM-based learning the PjBL model has an average value of M = 1.87 which means that it is fully implemented; the responses of students and teachers were very positive with a percentage of 90.91% and 85.25%. Learning Devices also meet the effective criteria because the class completeness reaches 84.85% and the n-gain results in increasing interest in learning are in the medium criteria.